2006
DOI: 10.1159/000090451
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining the Redox-Balance Intact: Gosha-Jinki-Gan but Not Insulin Activates Retinal Soluble Guanylate Cyclase in Diabetic Rats

Abstract: Strategies to prevent hyperglycemia-induced cytotoxic reactive oxygen species in the retina include the prevention of free radical production, activation of radical-scavenging capacities and inhibition of aldose reductase. This study examined the effect of the standardized Japanese herbal extract product gosha-jinki-gan (GJG) in comparison to insulin treatment in the rat retina. Diabetes was induced in male Wistar rats by single injection of streptozotocin (50 mg/kg i.p.). At 6 and 12 weeks, eyecups were remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
0
6
0
1
Order By: Relevance
“…Acrolein-amino conjugates involving, for example, lysine d-amino groups, 3-formyl-3,4-dehydropiperidine (FDP), 7 or 3-methylpyridinium (MP) derivatives 10 have been described (see the structure of FDP illustrated in Scheme 4). Antibodies 11 to these conjugates are widely used for the immunochemical detection of a variety of disease states, such as arteriosclerosis, [11][12][13][14] Alzheimer's disease, 15,16 tumors, [17][18][19][20][21] diabetes, [22][23][24][25][26] autoimmune disease, 27,28 high blood pressure, 29 among other diseases. [30][31][32][33][34] Alternatively, acrolein can react with polyamines to produce FDP conjugates that modulate the cytotoxicity of acrolein.…”
Section: Introductionmentioning
confidence: 99%
“…Acrolein-amino conjugates involving, for example, lysine d-amino groups, 3-formyl-3,4-dehydropiperidine (FDP), 7 or 3-methylpyridinium (MP) derivatives 10 have been described (see the structure of FDP illustrated in Scheme 4). Antibodies 11 to these conjugates are widely used for the immunochemical detection of a variety of disease states, such as arteriosclerosis, [11][12][13][14] Alzheimer's disease, 15,16 tumors, [17][18][19][20][21] diabetes, [22][23][24][25][26] autoimmune disease, 27,28 high blood pressure, 29 among other diseases. [30][31][32][33][34] Alternatively, acrolein can react with polyamines to produce FDP conjugates that modulate the cytotoxicity of acrolein.…”
Section: Introductionmentioning
confidence: 99%
“…For retinopathy, Cameron-Schaefer et al showed the protective effect of goshajinkigan against the diabetic retinopathy [22]. They showed that lipid peroxidation was enhanced by streptozotocin-induced hyperglycemia and that goshajinkigan prevented lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Moreover, GJG had shown protective effects against diabetic complications in the animal model or clinical setting. 15 , 16 , 17 Watanabe et al 16 showed that GJG had some beneficial effects on serum glucose and glycated hemoglobin. Comparing the medications in two groups, they found that the patients in the control group had more progressed medications in 5 years (nonmedication to medication or medication to insulin).…”
Section: Discussionmentioning
confidence: 99%